Clinical significance of pathological eye movements in diagnosing posterior fossa stroke. (September 2013) - Su, Chia-Hung; Young, Yi-Ho
Abstract Conclusion: Close observation of pathological eye movements such as disconjugate eye movements, multi-directional gaze nystagmus, and persistent unilateral gaze nystagmus may facilitate the effort of clinicians to arrange magnetic resonance imaging (MRI) study, because physical examinations may overlook the posterior fossa lesions. Objective: This paper reviews our experience of patients with posterior fossa stroke via observation of pathological eye movements over the past 10 years. Methods: Seventy patients with posterior fossa stroke manifested as acute vertiginous attack were admitted. All patients underwent examination of eye movements, MRI, and a battery of audiovestibular function tests. Results: Of the 70 patients, 22 (31%) demonstrated pathological eye movements including persistent (>24 h) unilateral gaze nystagmus in 12 patients, and multi-directional gaze nystagmus in 10 patients. Conjugate eyes movements were identified in 18 patients, and disconjugate eye movements were shown in 4 patients including medial longitudinal fasciculus syndrome in 1, paramedian pontine reticular formation syndrome in 1, and one and a half syndrome in 2. The vestibular test battery revealed abnormal responses for >85% of the patients in each test. MRI demonstrated infarction or hemorrhage involving the brainstem in 12 patients, cerebellum in 8 patients, and both in 2 patients.